Оцінювання перспектив розвитку стартап-індустрії України як драйвера інноваційного зростання в цифровій економіці - Ілляшенко, Сергій Миколайович; Шипуліна, Юлія Сергіївна; Ілляшенко, Наталія Сергіївна (My University, 2026)
Статтю присвячено оцінювання перспектив розвитку стартап-індустрії України як драйвера інноваційного зростання в цифровій економіці. Визначено порядок взаємовідносин і взаємодії стартап-індустрії та стартап-екосистеми країни з міжнародним бізнес-середовищем. Визначено і обґрунтовано сильні і слабкі сторони стартап-екосистеми України, а також створені міжнародним бізнес-середовищем можливості і загрози для розвитку стартап-індустрії країни. Методом SWOT-аналізу (авторська версія) визначено пріоритетні напрямки розвитку стартап-індустрії України в цифровій економіці для реалізації яких є зовнішні і внутрішні умови. Деталізовано сутність обраних пріоритетних напрямів розвитку стартап-індустрії України у секторальному розрізі, показано роль національної стартап-екосистеми у сприянні розвитку виділених секторів. Обґрунтовано перспективи ряду секторів стартап-індустрії стати драйверами інноваційного розвитку галузей національної економіки на засадах цифровізації. Окреслено і деталізовано загрози для обраних пріоритетних напрямів розвитку, зазначено способи протидії загрозам.

The article is devoted to the assessment of the prospects for the development of the startup industry of Ukraine as a driver of innovative growth in the digital economy. The manner of the relationship and interaction of the startup industry and the startup ecosystem of the country with the international business environment is determined. It is shown that the assessment of the prospects and the selection of priority areas for the development of the national startup industry should be carried out taking into account its relationships and interaction with the national startup ecosystem and the international business environment. The strengths and weaknesses of the startup ecosystem of Ukraine are determined and substantiated, as well as the opportunities and threats created by the international business environment for the development of the startup industry of the country. Using the SWOT analysis method (author's version), an assessment was made by a verbal-numerical scale of the degree of influence of the strengths and weaknesses of the national startup ecosystem of Ukraine on the prospects for realizing opportunities and countering threats in the international business environment. The assessment was carried out both in terms of the impact of individual indicators of strength and weakness and in terms of their complexes. This made it possible to determine the priority areas of development of the startup industry of Ukraine in the digital economy, based on external and internal conditions. The essence of the selected priority areas of development of the startup industry of Ukraine in a sectoral context is detailed, the role of the national startup ecosystem in promoting the development of selected sectors is shown. The prospects substantiated for a number of sectors of the startup industry, primarily MilitaryTech and DeepTech turn them to become drivers of innovative development of industries of the national economy on the basis of digitalization. Innovative developments in the indicated sectors initiated a radical modification of existing ones and the creation of new industries of the national economy. Threats to selected priority areas of development are outlined and detailed, and ways to counter threats are indicated. The results obtained form the information and analytical support for the organizational and economic mechanism for managing the development of the startup industry of Ukraine, which is considered a driver of innovative growth of the national economy in the conditions of technological transformations and turbulence caused by the fourth industrial revolution and digitalization.
Assessment of the prospects for the development of the startup industry of Ukraine as a driver of innovative growth in the digital economy
Keywords: стартап-екосистема; стартап-індустрія; міжнародне бізнес-середовище; інноваційний розвиток; четверта промислова революція; цифрова економіка; startup ecosystem; startup industry; international business environment; innovative development; fourth industrial revolution; digital economy